Assistance in Utilizing Instagram Insight in Evaluating Customer Characteristics and Preferences in MSMEs - Dwi Puspita Anggraeni (Abdimas Paspama, 2023)
This mentoring activity aims to increase Nielstuff MSME market penetration through optimizing the use of social media, especially Instagram. Initial observations show that MSMEs only use Facebook and Instagram as promotional media, with consistency problems and a lack of utilization of business features. Service activities are carried out online with a focus on training on the use of Instagram to support product sales. Activity material includes opening an online store, account promotion, content creation, and Instagram Insight analysis. The results of the assistance show an increase in interactions and impressions of the NiellStuff Instagram account, with positive insight graphs. Evaluation of activities confirms that MSMEs have the potential to develop their business through Instagram consistently. The hope is that these findings can help MSMEs optimize social media as an effective strategy in increasing product visibility and sales.